AB0788 Decrease of Muscle Strength is Associated with Increase of Activity Limitations in Early Knee Osteoarthritis: 3-Year Results from the CHECK Study. (10th June 2014) - Van Der Esch, M.; Holla, J.; van der Leeden, M.; Knol, D.; Lems, W.; Roorda, L.; Dekker, J.
Abstract : Background: Muscle weakness has been hypothesized as being an important factor in the development of activity limitations in knee osteoarthritis (OA). Longitudinal evidence to support this hypothesis is scarce in early knee OA. The direct association between change in muscle strength and change in activity limitations following exercise therapy in established knee OA was studied in randomized controlled trials 1–2 . These studies provided conflicting results. Objectives: The aims of the study were: 1) to determine whether a decrease in muscle strength over three years is associated with an increase in activity limitations; and 2) to examine whether the longitudinal association between muscle strength and activity limitations is moderated by knee joint proprioception and laxity in early symptomatic knee OA. Methods: A longitudinal cohort study with three-year follow-up. Subjects (N=146) with early symptomatic knee OA from the CHECK study. Measurements were performed at the second (T0) and fifth (T1) year of the Cohort Hip and Cohort Knee (CHECK) study. Muscle strength, proprioception and laxity were assessed using specifically designed measurement devices. Self-reported and performance-based activity limitations were measured with the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), the get-up-and-go test, walk-test and stair-climb test. Statistical analyses included paired t- tests, Chi-square tests and regression analyses. In regression analyses, the association between muscle strength and activity limitations was adjusted for relative confounders. Results: Overall, small 3-year changes in muscle strength and activity limitations were observed. A 3-year decrease in muscle strength was independently associated with an increase in performance-based activity limitations, on three measures. Proprioception and laxity did not moderate this association. Conclusions: In patients with early knee OA, a decrease in muscle strength is associated with an increase in activity limitations. Our results are a step forward in understanding the role of muscle weakness in the development of activity limitations in knee OA. To establish the causal role of muscle weakness in activity limitations, further well-designed experimental studies are indicated. References: Fitzgerald GK, White DK, Piva SR. Associations for change in physical and psychological factors and treatment response following exercise in knee osteoarthritis: an exploratory study. Arthritis Care Res (Hoboken). 2012;64(11):1673-80. Petersen SG, Beyer N, Hansen M, Holm L, Aagaard P, Mackey AL, Kjaer M. Nonsteroidal anti-inflammatory drug or glucosamine reduced pain and improved muscle strength with resistance training in a randomized controlled trial of knee osteoarthritis patients. Arch Phys Med Rehabil 2011;92(8):1185-93. Acknowledgements: CHECK is funded by the Dutch Arthritis Association. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5026